Towards definitions of critical illness and critical care using concept analysis. Issue 9 (5th September 2022) - Kayambankadzanja,, Raphael Kazidule; Schell, Carl Otto; Gerdin Wärnberg, Martin; Tamras, Thomas; Mollazadegan, Hedi; Holmberg, Mats; Alvesson, Helle Molsted; Baker, Tim
Abstract : Objective: As 'critical illness' and 'critical care' lack consensus definitions, this study aimed to explore how the concepts' are used, describe their defining attributes, and propose potential definitions. Design and methods: We used the Walker and Avant approach to concept analysis. The uses and definitions of the concepts were identified through a scoping review of the literature and an online survey of 114 global clinical experts. We used the Arksey and O'Malley framework for scoping reviews and searched in PubMed and Web of Science with a strategy including terms around critical illness/care and definitions/etymologies limited to publications in English between 1 January 2008 and 1 January 2020. The experts were selected through purposive sampling and snowballing, with 36.8% in Africa, 25.4% in Europe, 22.8% in North America, 10.5% in Asia, 2.6% in South America and 1.8% in Australia. They worked with anaesthesia or intensive care 59.1%, emergency care 15.8%, medicine 9.5%, paediatrics 5.5%, surgery 4.7%, obstetrics and gynaecology 1.6% and other specialties 3.9%. Through content analysis of the data, we extracted codes, categories and themes to determine the concepts' defining attributes and we proposed potential definitions. To assist understanding, we developed model, related and contrary cases concerning the concepts, we identified antecedents and consequences to the concepts, and defined empirical referents. Results: Nine and 13 articles were included in the scoping reviews of critical illness and critical care, respectively. A total of 48 codes, 14 categories and 4 themes were identified in the uses and definitions of critical illness and 60 codes, 13 categories and 5 themes for critical care. The defining attributes of critical illness were a high risk of imminent death; vital organ dysfunction; requirement for care to avoid death; and potential reversibility. The defining attributes of critical care were the identification, monitoring and treatment of critical illness; vital organ support; initial and sustained care; any care of critical illness; and specialised human and physical resources. The defining attributes led to our proposed definitions of critical illness as, 'a state of ill health with vital organ dysfunction, a high risk of imminent death if care is not provided and the potential for reversibility', and of critical care as, 'the identification, monitoring and treatment of patients with critical illness through the initial and sustained support of vital organ functions.' Conclusion: The concepts critical illness and critical care lack consensus definitions and have varied uses. Through concept analysis of uses and definitions in the literature and among experts, we have identified the defining attributes of the concepts and proposed definitions that could aid clinical practice, research and policy-making.